ANALISIS MODAL SOSIAL DALAM PENGELOLAAN DESA WISATA NONGKOSAWIT KOTA SEMARANG - Setiyo Budi Pamungkas; Budi Puspo Priyadi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The condition of the Nongkosawit tourist village during the past six years, could be said to be still premature. The Elimination of the budget for village tourism program in the year 2018 undermines Nongkosawit tourist village to look forward to the Government. Thus the Nongkosawit tourist village had to dig social capital to get another alternative in management. The purpose of this research was to identify the social capital as well as analyze the driving factor and a barrier to social capital in the management of Nongkosawit tourist village. An attempt to answer the problem and research objectives is done using the theory of social capital through qualitative methods. The research subjects were a Kandang Gunung group, Department of Culture and Tourism Semarang City, and the people of Nongkosawit tourist village. The results showed that social capital in the management of the Nongkosawit tourist village have no impetus to build tourism potential. Custom factors became the driving factor and the factor of the position and the role of the individual; education; social class and economic disparities; and patterns of consumption and personal values into the factors restricting the development of social capital in the management of Nongkosawit tourist village. It is recommended to the Government of the Semarang City and/or through the Department of culture and tourism should be more selective in linking the proposed community groups who filed his village as a tourist village. Need for institutional reorganizing the Kandang Gunung Group. Turn of the Chairman and of the range of Kandang Gunung Group is required to be able to drive or urge people to engage actively in the management of the Nongkosawit tourist village.